The spring durum wheat variety ‘Bezenchuksky Podarok’ - P. N. Malchikov; M. G. Myasnikova; T. V. Chakheeva (Зерновое хозяйство России)
The purpose of the current study was to determine the main economically valuable traits of the new spring durum wheat variety ‘Bezenchuksky podarok’, to establish its significance in the system of durum wheat varieties and to describe the main approbation traits. The variety was developed by individual selection from the hybrid population F9 746D-39/Pamyati Chekhovicha. Its pedigree includes such varieties as ‘Kharkovskaya 46’, ‘Bezenchuksky yantar’, ‘Saratovskaya zolotistaya’, ‘CIMMYT – Altar 84’, ‘Ahninga’, intermediate breeding lines ‘92D-4’, ‘2125D-4’, ‘746D-18’ of the Samara RIA and the breeding line ‘358s-94’ of the RIA of the South-East. Field trials, phenological observations and estimations in the competitive and ecological variety trials were carried out in accordance with the requirements of the methodology of the State Commission for Variety Testing and Protection of Breeding Achievements. The variety belongs to the Volga steppe ecological group, middle-maturing biotype, having a medium-sized stem (with the height reduction gene RhtAhng). Over the years of study (2018–2022), in the competitive variety testing, a new variety with a mean grain productivity of 2.36 t/ha exceeded the standard variety ‘Bezenchukskaya 210’ on 0.15 t/ha and the variety ‘Bezenchukskaya zolotistaya’, which is widespread in the Volga region and the Urals, on 0.19 t/ha. In the ecological variety testing in the Samara SAU (Kinel) and in the RIA of the South-East (Saratov), the excess over local standards was 1.05 t/ha and 0.06 t/ha, respectively. In the competitive variety testing (2018–2022), the new variety was the best in its responsiveness to environmental conditions (the regression coefficient bi was 1.06, the standard variety’s coefficient was 1.00), and its resistance to stem rust pathogens and leaf spots (Alternaria sp., Fusarium sp.). The new variety was the best in terms of gluten quality with the parameters of SDS (52 ml), and IG (94.0 %), which makes it possible to attribute it to the class of durum wheat varieties with excellent gluten. Thus, gluten quality and production capabilities of the variety ‘Bezenchuksky Podarok’ have enhanced the diversification of the durum wheat varietal system in the Middle Volga region.